The Unmet Need of Olfactory Testing in Inflammatory Disorders of the Upper Airways-An EAACI Position Paper. - Klimek,L; Mullol,J; Hummel,T; Del,Giacco S; Georgalas,C; Rondon,C; Schiappoli,M; Gevaert,P; Bozkurt,B; Chaker,A; Reitsma,S; van,Gerven L; et al. (Allergy, 2026)
The sense of smell, with its extensive evolutionary history, is highly prone to disorders that can have a profound impact on daily life. Anosmia affects approximately 5% of the population, with an additional 15% exhibiting reduced olfactory function. The prevalence of olfactory dysfunction (OD) varies by population and age group, and standardized testing reveals a broad range of impacts. OD includes various causes, most commonly aging, inflammation of the olfactory epithelium, upper respiratory tract infections (URTI), traumatic brain injury, and neurological conditions. The recent COVID-19 pandemic has highlighted the association between viral infections and olfactory dysfunction, with severe hyposmia/anosmia being an early marker of infection. Despite its importance, the assessment of olfactory function remains inconsistent across clinical practices. Psychophysical smell tests, while vital for diagnosis and patient management, are underutilized, especially outside of specialized centers. Standardized testing methods are crucial for objective diagnosis, but significant challenges, including test variability, lack of comparability, and healthcare reimbursement issues, persist. The European Academy of Allergy and Immunology (EAACI) advocates for improvements in the quality and standardization of chemosensory assessments. Future efforts must prioritize education, incentives for better testing, and the integration of digital tools to expand access to olfactory testing and diagnosis in remote or quarantine situations. However, office-based testing remains irreplaceable, even with advancements in telemedicine.